Analytical study of cause and risk factors of severe anemia in third trimester of pregnancy at tertiary care center - Agarwal, Juhi; Meravi, Archana; Badkur, Poorva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anemia during pregnancy is a global public health challenge facing the world today. Among the South Asian countries, WHO estimate that India has the highest prevalence of anemia in pregnancy. Prevalence of anemia in pregnant Indian women is 49.7%, against the global prevalence of 41.8% (WHO 2008). In India, the prevalence of anemia is high because of ignorance, poverty, fewer intakes of iron, folic acid and food sources and gender bias significantly contribute to this high prevalence. Hence, this study aims to identify the risk factors and red cell morphological pattern that contribute to the presence and severity of anemia among pregnant women at the Sultania Zanana hospital, Gandhi Medical College Bhopal. Methods: The present study was conducted in Department of Obstetrics and Gynaecology, Sultania Zanana Hospital, Gandhi Medical College, Bhopal, Madhya Pradesh, India. The study included all pregnant women at third trimester who was admitted at Sultania Zanana hospital, Bhopal from January 2016 to December 2016 having haemoglobin level < 7 gm /dl. This is a Hospital- based Observational study. The sample size was calculated to be 500. Results: The following conclusion were drawn from this study. Poverty, early marriage, multiparity, poor nutrition, parasitic infections and lack of antenatal visits and antenatal care due to illiteracy and ignorance are probably the most important features responsible for severity of anemia. Maximum patients of anemia were in the age group of 21-35 Years. The majority of patients (62.8%) were rural. Majority of cases (65.4) belongs to low-socioeconomic class followed by (29.8%) belongs to middle socio-economic category. Most of the patients were multigravida (68.6%) most of them came from poor and illiterate class of society (74.2%) followed by women less than 20-year-old (18.8%). Majority of patients had education level (43.0%) below 10th standard. Conclusions: This study was undertaken to find out the various risk factors that contribute to the severity of anemia.